We the people : the Fourteenth Amendment and the Supreme Court - Perry, Michael J. (OUP E-Books., 1999)
Several of the most divisive moral conflicts that have beset Americans in the period since World War II have been transmuted into constitutional conflicts and resolved as such. In his new book, eminent legal scholar Michael Perry evaluates the grave charge that the modern Supreme Court has engineered a "judicial usurpation of politics." In particular, Perry inquires which of several major Fourteenth Amendment conflicts - over race segregation, race-based affirmative action, sex-based discrimination, homosexuality, abortion, and physician-assisted suicide - have been resolved as they should have been. He lays the necessary groundwork for his inquiry by addressing questions of both constitutional theory and constitutional history. A clear-eyed examination of some of the perennial controversies in American life, We the People is a major contribution to modern constitutional studies.